ANALISIS iYURIDIS iKEWENANGAN iKEPALA iDESA iDALAM PEMBERHENTIAN PERANGKAT DESA (Studi Putusan Nomor 75/G/2020/PTUN.Sby) - Selestinus Baene (Jurnal Panah Hukum, 2023)
Village apparatus is a staff member who assists the village secretariat, and elements supporting the village head’s duties in carrying out policies that are organized in the form of implementation and regional elements. The Surabaya State Aministrative court, namely decision number 75/G/2020/PTUN.Sby. in this decision, the devendant is required to rehabilitate, restore the dignity of the plaintiffs and punish the defendant to pay the costs of the case jointly and severally in the amount of Rp. 382,000,- (three hundred eighty two thousand rupiah). The type of research used is normative legal research with statutory regulations, case approaches and analytical approaches. The data analysis used was descriptive qualitative data analysis and conclusions were drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the judge’s decision in imposing a sentence on the defendant (decision number 75/G/2020/PTUN.Sby) is unfair where the defendant’s actions are not comparable to the required sentence. The defendandt should also be obliged to pay what is the right of the plaintiffs during their dismissal as village officials. The author suggests that the panel of judges who examined and decided on cases of dismissal of village officials to be more careful in imposing punishments commensurate with the actions of the defendandt against the plaintiff